Kemampuan Mobilisasi Dini Dan Tingkat Nyeri Pasien Post Sectio Caesarea Dengan Metode ERACS Di RSIA Azzahra Palembang - Ranida Arsi; Annisa Rizkiyani; Eka Rora Suci Wisudawati; Andre Utama saputra (Jurnal Ilmiah Keperawatan STIKES Hang Tuah Surabaya, 2025)
The ERACS method is the latest birthing method resulting from innovation and development of the ERACS (Enhanced Recovery After Caesarea Section) concept. With the ERACS method, patients can mobilize as early as possible and also overcome post-operative pain. Mobilization is a person's ability to move freely and is a prominent factor in accelerating recovery after surgery and anesthesia. While post-operative pain is something that is feared by patients, pain also causes patients to be afraid to move and do activities, especially in the first 24 hours after surgery. The purpose of this study was to determine the ability of early mobilization and pain in post-cesarean section patients with the ERACS method at RSIA Azzahra Palembang in 2024. This study used a descriptive analytical design with a cross-sectional approach. The sample collected was 77 respondents with the accidental sampling technique. The data analysis carried out was Univariate Analysis where out of 77 patients, 74 respondents were able to mobilize early and 3 patients were unable to mobilize early while for pain from 77 respondents, 72 respondents experienced mild pain and 5 respondents experienced moderate pain. From the results of this study, it can be concluded that patients are able to perform early mobilization and are free from post-cesarean section pain using the eracs method at RSIA Azzahra Palembang.